Makna Rendahnya Motivasi Siswa Belajar Geografi Dalam Pendekatan Fenomenologi - Farina Amelia; I Nyoman Ruja; Singgih Susilo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2018)
Abstract: Schutz perspective phenomenological approach becomes an appropriate alternative to this research because understanding not apart from because motive and in order to motive. Research subjects in this study were students of class XII. Data collection techniques used include observation, interviews, and documentation. The results showed that the meaning of geography learning for students who have low motivation to learn geography is geography is a difficult subject, boring, and less perceived benefits for everyday life but must be studied in order to get a good value.